Elementary Teachers' Perceptions on Genially Learning Media Using Item Response Theory (IRT) - Neni Hermita; Zetra Hainul Putra; Jesi Alexander Alim; Tommy Tanu Wijaya; Subuh Anggoro; Diniya Diniya (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
Many studies have developed learning media, but few studies focus on developing learning media in ele-mentary schools using Genially and studying teachers' perceptions of Genially learning media. This study aims to determine teachers' perceptions of hybrid learning media with a more accurate and precise method, namely the item response theory (IRT) from the Rasch model. The survey was carried out by distributing a Likert scale questionnaire of 19 statements. Moreover, the subjects were 45 elementary school teachers in Riau Province, Indonesia. The results showed that they positively perceived the developed genially-based learning media. Genially learning media can support teachers in teaching. Based on these results, teachers need to develop skills in making various technology-based media, in order to support hybrid learning.